Data Against Hate – Processing of Personal Data Revealing Racial or Ethnic Origin for the Purpose of Combating Hate Crime in the European Union - Török, Tamás (Pécs journal of international and European law, 2023)
Combating hate crime and preventing discrimination on the grounds of racial or ethnic origin is a commitment of the European Union, and has been the subject of significant legislative and policy action over the past decades. However, the judgments of the European Court of Human Rights and the policy review have made it clear that these measures have not achieved their objectives, and one of the main reasons for this is the problem of identifying the groups concerned. Data relating to racial or ethnic origin is a special category of personal data that enjoys special protection under the EU data protection regime, but it is also very complex to handle. This data set expresses the identity of the data subject and is therefore partly subjective and difficult to measure. In addition, the volume, quality and source of the data required for each purpose is challenging, while the legal framework for the process is also different: general data processing issues are governed by the GDPR, while law enforcement cases are governed by the Criminal Justice Directive. Although regional human rights organisations clearly support for the collection of racial or ethnic data for its political benefits, EU case law is fragmented. But could legislation or enforcement be the main cause of this worrying situation? Are legal or social science tools the key to more effective data management? The paper attempts to answer these questions by describing the elements of the system and by presenting the practicalities. The analysis also leads to the necessary intervention points and a system of possible measures.